38.1: Efficiency Enhancement of Organic Light‐Emitting Diodes on Flexible Substrate with Patterned Inverted Cone Structure. Issue 1 (June 2015) - Wang, Yi‐Jun; Ouyang, Shi‐Hong; Lu, Jian‐Gang; Shieh, Han‐Ping D.
Abstract : A patterned inverted cone (PIC) structure on flexible substrate produced by focused femtosecond laser was demonstrated for the out‐coupling efficiency enhancement of electroluminescent devices. A green Organic Light‐Emitting Diode (OLED) with PIC structure on flexible substrate was employed to verify the effect of the proposed method, which exhibited a current efficiency enhancement by a factor of 2.2 at 10 mA/cm 2 without any emission spectrum altered, compared with conventional flexible OLED. The PIC structure is compatible with current device fabrication process and applicable for full color OLED display and lighting.